Rapid, sensitive, and visual detection of porcine rotavirus with RPA-CRISPR/Cas13 - Mi, Yong; Dai, Mingyang; Xing, Xiaokun; Zhang, Yang; Xu, Zhiwen; Zhu, Ling (Frontiers in Microbiology, 2025)
Porcine rotavirus (PoRV) is one of the major pathogens causing viral enteritis in piglets, posing serious threats to the pig industry and public health. Existing pathogen detection methods, such as RT-qPCR, suffer from complex procedures and strong reliance on equipment, making them difficult to meet the needs of grassroots laboratories or field detection. Therefore, in this study, a novel rapid and visual detection platform, was developed based on the CRISPR/Cas13 system. This platform integrates Recombinase Polymerase Amplification (RPA), T7 transcription, CRISPR trans-cleavage, and fluorescence signal output. Targeting the PoRV VP6 gene, it achieves highly sensitive and specific detection of PoRV without the need for large equipment. The optimized system has a minimum detection limit of 101 copies/μL for standard plasmids, and it was validated with 62 clinical diarrheal samples, yielding results consistent with RT-qPCR, demonstrating good clinical applicability. This platform is simple to operate, intuitive in detection, and cost-effective, making it suitable for rapid field screening of PoRV in resource-limited areas. It provides robust technical support for early diagnosis and epidemiological investigation of porcine rotavirus.